A multicriteria function for polymer gear design optimization. Issue 2 (14th January 2021) - Tavčar, Jože; Černe, Borut; Duhovnik, Jože; Zorko, Damijan
Abstract: A reliable method of optimization of polymer gears remains, to date, an open challenge, due to the lack of specific material characterization of polymers and to the complex nonlinear relations between different geometric and operating parameters. For spur and helical gears, the authors herein have developed the optimization algorithm, which primarily enables variation of geometry according to various criteria: the number of teeth ( z 1, z 2 ), face width ( b ), helix angle ( β ), and normal module ( m n ). The method enables a better insight into how design parameters influence the target criteria. The main paper contribution is a newly developed multicriteria function that enables a simultaneous consideration of different criteria such as root/flank stress, gear bulk/flank temperature, wear, deformation, quality, cost, and volume. Graphical Abstract: